Synthesis of 1-(N-stituted-Carboxamido-2-Aminophenyl)4-Methyl-Piperazines: D.E.C. Analogs and Their Antifilarial Activity-II - Beg, M.S.J.; Singh, B.N.; Raj, Prem (Asian Journal of Chemistry, 2012)
A series of 1-(N-stituted-carboxamido-2-amino phenyl 4-methyl piperazines (I-IX) have been synthesized and tested for their antifilarial activity; compounds III, V, VI have exhibited 76.8, 72.4 and 75% microfilaricidal activity respectively.